Encephalitozoon cuniculi and Vittaforma corneae (Phylum Microsporidia) inhibit staurosporine-induced apoptosis in human THP-1 macrophages in vitro. Issue 5 (29th November 2018) - Sokolova, Yuliya Y.; Bowers, Lisa C.; Alvarez, Xavier; Didier, Elizabeth S.
Abstract: Obligately intracellular microsporidia regulate their host cell life cycles, including apoptosis, but this has not been evaluated in phagocytic host cells such as macrophages that can facilitate infection but also can be activated to kill microsporidia. We examined two biologically dissimilar human-infecting microsporidia species, Encephalitozoon cuniculi and Vittaforma corneae, for their effects on staurosporine-induced apoptosis in the human macrophage-differentiated cell line, THP1. Apoptosis was measured after exposure of THP-1 cells to live and dead mature organisms via direct fluorometric measurement of Caspase 3, colorimetric and fluorometric TUNEL assays, and mRNA gene expression profiles using Apoptosis RT 2 Profiler PCR Array. Both species of microsporidia modulated the intrinsic apoptosis pathway. In particular, live E. cuniculi spores inhibited staurosporine-induced apoptosis as well as suppressed pro-apoptosis genes and upregulated anti-apoptosis genes more broadly than V. corneae. Exposure to dead spores induced an opposite effect. Vittaforma corneae, however, also induced inflammasome activation via Caspases 1 and 4. Of the 84 apoptosis-related genes assayed, 42 (i.e. 23 pro-apoptosis, nine anti-apoptosis, and 10 regulatory) genes were more affected including those encoding members of the Bcl2 family, caspases and their regulators, and members of the tumour necrosis factor (TNF)/TNF receptor R superfamily.